Identifikasi dan Pengendalian Risiko Keselamatan Kerja pada Pengoperasian Mesin Rotogravure Menggunakan Metode HIRARC dan FTA - Fadilah Juliani; Ferida Yuamita (KAMPUS AKADEMIK PUBLISING, 2026)
The operation of rotogravure machines involves various hazards that may increase the risk of occupational accidents if not properly controlled. This study aims to identify potential hazards, assess occupational risk levels, and propose risk control measures for rotogravure machine operations at PT IGP Internasional Sleman using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) and Fault Tree Analysis (FTA) methods. A descriptive research approach was employed, with data collected through observation, interviews, and documentation. The results indicate that hazards were identified during roller setting, printing, dryer operation, and machine cleaning activities. Based on the HIRARC assessment, roller setting was classified as High Risk, while printing and dryer operations were categorized as Moderate Risk, and machine cleaning as Low Risk. FTA revealed that occupational accidents were primarily influenced by human factors, machine conditions, work methods, and inadequate implementation of safety practices. The recommended control measures include improving compliance with standard operating procedures, consistent use of personal protective equipment, regular occupational safety training, workplace supervision, and routine machine maintenance.